2012
DOI: 10.1124/jpet.112.195156
|View full text |Cite
|
Sign up to set email alerts
|

The Serotonin 2C Receptor Antagonist SB 242084 Exhibits Abuse-Related Effects Typical of Stimulants in Squirrel Monkeys

Abstract: Antagonists of the serotonin (5-hydroxytryptamine; 5-HT) type 2C receptor (5-HT 2C R) are being considered as potential pharmacotherapeutics for various affective disorders, but evidence suggests that these compounds enhance the effects of cocaine and related psychostimulants in rodents. However, the effects of selective 5-HT 2C R antagonists have not been evaluated in nonhuman primates. The present studies used operant-behavioral and in vivo microdialysis techniques to assess the impact of 5-HT 2C R antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 42 publications
4
33
2
Order By: Relevance
“…Systemic administration of the 5-HT 2C R agonist, Ro 60-0175, significantly attenuated cocaine-induced increases in extracellular DA in the NAc of conscious squirrel monkeys at a dose that attenuated cocaine self-administration and cocaineinduced reinstatement of previously-extinguished cocaine self-administration (Manvich et al, 2012a). Conversely, systemic administration of the selective 5-HT 2C R antagonist, SB 242084, enhanced cocaine-induced increases in NAc DA at a dose that enhanced cocaine-induced reinstatement and maintained self-administration when substituted for cocaine (Manvich et al, 2012b). The latter finding is consistent with a previous study demonstrating that systemic administration of SB 242084 enhanced cocaine-induced increases in DA in the NAc in rats .…”
Section: B Cocaine Effects On Dopamine Neurochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…Systemic administration of the 5-HT 2C R agonist, Ro 60-0175, significantly attenuated cocaine-induced increases in extracellular DA in the NAc of conscious squirrel monkeys at a dose that attenuated cocaine self-administration and cocaineinduced reinstatement of previously-extinguished cocaine self-administration (Manvich et al, 2012a). Conversely, systemic administration of the selective 5-HT 2C R antagonist, SB 242084, enhanced cocaine-induced increases in NAc DA at a dose that enhanced cocaine-induced reinstatement and maintained self-administration when substituted for cocaine (Manvich et al, 2012b). The latter finding is consistent with a previous study demonstrating that systemic administration of SB 242084 enhanced cocaine-induced increases in DA in the NAc in rats .…”
Section: B Cocaine Effects On Dopamine Neurochemistrymentioning
confidence: 99%
“…Furthermore, by comparing the effects of a preferential agonist, m-chlorophenylpiperazine, with those of Ro 60-0175 on nondrug-maintained operant responding, the results indicated that increased pharmacological selectivity for the 5-HT 2C R confers a higher index of behavioral specificity, because Ro 60-0175 more potently altered cocaine-maintained versus nondrug-maintained behavior. In complete opposition to the behavioral effects of 5-HT 2C R agonist administration, pretreatment with the selective 5-HT 2C R antagonist SB 242084 induced modest behavioral-stimulant effects when administered alone, potentiated the behavioralstimulant effects of cocaine in an additive manner, and enhanced the reinstatement effects of cocaine in squirrel monkeys (Manvich et al, 2012b). The study also evaluated whether intravenous infusions of SB 242084 would maintain responding in squirrel monkeys when substituted for cocaine in self-administration sessions.…”
Section: Abuse-related Behavioral Effects Of Cocainementioning
confidence: 99%
See 2 more Smart Citations
“…Selective 5-HT2CR blockade produces opposite effects on self-administration of low doses of cocaine (Fletcher et al 2002a) and enhances cocaine-evoked reinstatement of drugseeking in rodents (Fletcher et al 2002a;Pelloux et al 2012). In non-human primates, 5-HT2CR agonism attenuated the stimulant, reinforcing and reinstatement effects of cocaine, which are blocked by the 5-HT2CR antagonist SB242084 (Manvich et al 2012a;2012b;Ruedi-Bettschen et al 2015). SB242084 itself may induce modest stimulant effects in primates (Manvich et al 2012a;2012b), although this data is open for discussion (RuediBettschen et al, 2015).…”
Section: Addiction and Substance Use Disorders: Lorcaserinmentioning
confidence: 99%